PEMBERIAN SUSU SARI KACANG KEDELAI KEPADA IBU NIFAS TERHADAP PENINGKATAN PRODUKSI ASI - Rauda Rauda; Leli Diana Sari Harahap (Jurnal Keperawatan Priority, 2023)
Breast milk is a nutritional choice with the best quality and quantity for newborns. Lack of milk intake in infants can cause malnutrition. Most of the infant mortality in the world is caused by malnutrition. Postpartum mothers in Indonesia experience many problems with milk production. Several factors affect breast milk production; one of the most important is the food consumed by postpartum mothers. Indonesia is a tropical country, so there are many types of plants or fruits that can help increase milk production and levels of the hormone prolactin. Plants that increase milk production include soybeans. The research design used in this study was quasi-experimental with a one-group pretest-posttest design. The sample for this study was all postpartum mothers who met the inclusion criteria, which included as many as 15 people. Purposive sampling was used in this study. Data analysis used the Wilcoxon signed-rank test. The results showed that most respondents were in the working area of PMB Diana Tamdem Hilir Pasar and experienced an increase in milk production after being given soy milk, with fairly smooth milk production of 14 people (93%). The results of the different tests with a p-value = 0.001 indicate that there is a difference in milk production before and after giving soy milk extract. In conclusion, consuming soybean milk is very effective as an alternative for postpartum mothers who have a large amount of milk production and can increase the exclusive breastfeeding program